Investigation of the Effectiveness of Surgical Treatment on Respiratory Functions in Patients With Obstructive Sleep Apnea Syndrome - (:unkn) unknown (My University, 2020)
Objective: Obstructive sleep apnea syndrome (OSAS) is a problem that involves many bodily systems and its effects on the respiratory system deserve special attention. Although many studies exist that investigate respiratory functions in patients using continuous positive airway pressure (CPAP) for the treatment of sleep apnea, there is a lack of research regarding the effect of OSAS surgery on respiratory function in the literature, which has motivated us to perform such a study. Materials and Methods: Thirty-two patients diagnosed with OSAS with an apnea hypopnea index ranging between 15 and 30 and had undergone robotic tongue base resection and uvulopharyngoplasty were included as study participants. Pulmonary function tests were performed on all participants 1 day prior to, and at 3 and 6 months after the operation. Weight and body mass indices (BMIs) were also recorded at the same intervals for all participants. Data were electronically recorded and analyzed through SPSS 22.0. Values of P < .05 have been considered as statistically significant. Results: Average age of the 32 participants was 43.2±10.7, average body weight was 94.1±12.6, and average BMI was 31.4±4.7. Decreases in body weight and BMI values recorded at 3 and 6 months postoperatively had statistical significance when compared with values recorded preoperatively ( P < .05). Comparisons made in terms of pulmonary functions revealed a statistically significant increase in 3 and 6-month postoperative values of FVC, FEV1, FEV1/FVC, PEF, and FEF 25-75 ( P < .05). Conclusion: Our study shows the positive effects of robotic tongue base resection and uvulopharyngoplasty operation on respiratory function parameters. This suggests that surgical treatment in OSAS patients is as effective as CPAP on respiratory function.